Molecular diagnosis and possible control of the pathogenic Aspergillus flavus isolates associated with cultivated mushroom Agaricus bisporus in Iraq - Alzyadi , Haneen Muhy Salman; Alhamiri, Yasir naser Hussein (Journal of Kerbala for Agricultural Sciences, 2022)
Five isolates of Aspergillus flavus were isolated from casing soils, compost and fruiting bodies of Agaricus bisporus from several culture stations in Iraq. According to the pathogenicity test, the highest percentage of inhibition was recorded for isolate A.flavusB1 .It was molecularly diagnosed to the level of A.flavus on the basis of the nucleotide sequence analysis of the ITS genome region and I was recorded globally on the NCBI data base under the accession number ON738705.1. The effect of the hot aqueous extract of Cloves and Conocarpus, and the efficacy of the biocide VEROX on the production and phenotypic characteristics of the white edible fungus A. bisporus was studied in present of the pathogenic fungus. The results showed that the treatment of the combination of plant extracts + biocide + pathogenic fungus was recorded the highest rate of growth inhibition of the pathogenic fungus compared with other treatments ,and it was increased the number of fruiting bodies up to 505 compared with the control treatment of pathogenic fungus was 195. The total yield of the same treatment was 19.894 kg compared to 4.933 kg in the control treatment, and the biological efficiency was recorded by 33.7% compared to 12.6% in the control treatment. In general, this combination increased production and improved the qualitative characteristics of the fruiting bodies, as the average diameter of the cap was 43.1 mm and the stalk length was 39.1 mm compared to 28.5 mm and 23.5 mm in the control treatment, respectively.